Contribuições de um programa a distância sobre educação inclusiva para o desenvolvimento profissional do professor - Silva, Ione Arsenio da (2012)
This study deals with a research proposal and intervention that aimed to: develop, implement and evaluate a distance teacher training program on Inclusive Education. To that, it started with the following research question: What are the limits and possibilities of a distance continuing training program in education by the Internet to teachers of the early years of elementary school? The basis of the investigation was continuing education program for teachers entitled "Diversity in school: reflecting on pedagogical practices in inclusive classrooms ", developed through Portal dos Professores - UFSCar MOODLE platform. The whole program was online and it was aimed at elementary school teachers who work in early years, live all over the country, and had signed up spontaneously in the Teachers' Portal. Our study is suitable for a methodological form of research that focuses on collaborative research between researchers and teachers, recognizing that teachers get the knowledge from their practices and they know that is very important to link this knowledge with the one produced in academic circles. Our investigation, therefore, contemplates the purposes of collaborative action from a model of research and intervention called constructive - collaborative. Taking the narrative as the main form of data collection, data from this research were obtained from 16 teachers who participated during five months of the training process. After this study, we consider that the use of distance learning (EaD) by Internet is an important and interesting training resource. However, in order to it be actually an efficient way of training, some factors should be seen as the issue of self-government and discipline for studies that are very required when there is the participation in a program of distance education by Internet. These are essential skills for the student to take advantage of the program. So, it s important that programs adopt tools that provide moments of interaction among the participants themselves and between them and the teacher or tutor. The number of students per tutor, or teacher is another aspect to be observed because it affects the quality of the course. If there is a large number of participants, it is difficult to the monitor analyzes and observes the participation and learning of all of them. Observed these aspects, we believe in distance education by internet as an effective means of training, first because it keeps people who live in different places and away from the training place closer to each other and the course can be done at any time they want. Second, the web offers resources that can break a formation based on the simple transmission of content and the idea of passive learning.